Mother's Views about Efficacy of Prenatal Educational Classes to Prepare for Normal Vaginal Delivery, Postpartum and Breastfeeding - ّSomayeh Bahrami; Mojtaba Raji; Nosrat Bahrami (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Prenatal educations focusing on physical, emotional and mental preparation for delivery, health promotion and improving lifestyle behaviors in families during the reproductive years. In this education, parents achieve data about physical, emotional and mental changes during pregnancy delivery and postpartum and overcome skills. Aim of this study was to determine Comments mothers about efficacy prenatal education classes to prepare for normal vaginal delivery, postpartum and breastfeeding in women referring to Dezful health Centers, 2015 Materials and Methods: The descriptive study using quota sampling was performed. A total of 250 women consented to participant at study. A questionnaire was provided by content validity. It is reliability was confirmed by Test re-test. A questionnaire was used in 4 Part: demographics, knowledge toward mode of delivery and Comments mothers about efficacy prenatal education classes to prepare for normal vaginal delivery, postpartum and breastfeeding. Data using SPSS statistics software and analyzes were performed. Results: More women (54.2%) were moderate knowledge level. The majority of patients believed that prenatal classes aided there in preparation for natural childbirth (93.6%), the postpartum period (75.6%), and preparation for lactation (100%) Conclusion: The study showed that prenatal education has an important role on choosing the mode of delivery and preparing for vaginal delivery. So that approach this training and prenatal care to all pregnant women is recommended.